Silicon incorporated tacrine: design, synthesis, and evaluation of biological and pharmacokinetic parameters - Kulkarni, Akshay S.; Ramana, Sreenivasa Rao; Nuthakki, Vijay K.; Bhatt, Shipra; Jamwal, Ashiya; Nandawadekar, Laxman D.; Jotshi, Anshika; Kumar, Ajay; Nandi, Utpal; Bharate, Sandip B.; Reddy, D. Srinivasa (RSC Medicinal Chemistry, 2025)
Tacrine, an orally bioavailable cholinesterase inhibitor, was previously used to treat Alzheimer's disease but was withdrawn due to hepatotoxicity. The unique structural features of tacrine have once again captured the interest of medicinal chemists. However, the blood-brain barrier (BBB) permeability hampered the development of the majority of its new analogs. Herein, we employed a silicon switch approach for improving the BBB permeability of CNS drugs with tacrine as a tool compound. The replacement of C2 methylene of tacrine with dimethyl silicon yielded `sila-tacrine' that inhibits acetylcholinesterase as well as butyrylcholinesterase with IC50 values of 3.18 and 6.09 mu M, respectively. Sila-tacrine competitively inhibits acetylcholinesterase while it is a non-competitive inhibitor of butyrylcholinesterase. The molecular docking results corroborated with the in vitro cholinesterase inhibition activity of tacrine vs. sila-tacrine. Sila-tacrine demonstrated metabolic stability in HLM and MLM and exhibited superior plasma exposure in an oral pharmacokinetic study in Swiss albino mice. However, tissue distribution studies revealed lower-than-expected brain levels due to efflux pump-mediated transport. This study offers a proof-of-concept for the silicon switch approach in improving the BBB permeability of CNS-active compounds.